Education towards difference and inclusion. Two types of discourses —to positive pedagogy* - Kwieciński, Zbigniew (Wydawnictwo Naukowe UAM, 2014)
The main goal of this article is description of two educational discourses pertaining to differences, their acceptance and eradication or alleviation. The first is the special needs pedagogy, which has seen a dispute between the enthusiasts of institutional and social integration of the disabled with people, communities and institutions dominated by those within a given norm. The second is characteristic of the critical pedagogy and sociology—concerns people and social groups who are culturally and socially excluded and marginalised, both overtly and covertly.
Keywords: inclusion; special needs pedagogy; critical pedagogy; positive pedagogy